Intermittent micro-aeration: New strategy to control volatile fatty acid accumulation in high organic loading anaerobic digestion. (1st December 2019) - Nguyen, Duc; Wu, Zhuoying; Shrestha, Shilva; Lee, Po-Heng; Raskin, Lutgarde; Khanal, Samir Kumar
Abstract: This study developed an intermittent oxidation-reduction potential (ORP)-controlled micro-aeration system for high solids anaerobic digestion (AD) of lignocellulosic biomass without volatile fatty acids (VFA) accumulation at high organic loading rate (OLR). Traditional AD of Napier grass, a model lignocellulosic biomass, at an OLR of 5 g volatile solids (VS)/L/day resulted in an accumulation of total VFA concentration up to 9.2 g/L as acetic acid (HAc) equivalent, causing rapid drops in pH and methane yield, and driving the digester to the verge of failure. Once intermittent (every 24 h) ORP-controlled micro-aeration (at ORP of −470 mV) was initiated, the total VFA concentration rapidly decreased to 3.0 g HAc/L and the methane yield improved, resulting in stable digester performance without the need for alkalinity supplementation or OLR reduction. By combining reactor performance results, mass balance analyses, microbial community characterization data, and a bioenergetic evaluation, this study suggested that rapid VFA conversion and CH4 production were carried out by facultative anaerobes and hydrogenotrophic methanogens under micro-aerobic conditions. This novel operating approach can be applied as an effective control strategy for high OLR AD processes especially in the event of VFA accumulation. Graphical abstract: Image 1 Highlights: Increasing OLR resulted in accumulation of VFA and potential reactor failure. Micro-aeration reduced VFA concentration and recovered reactor performance. Micro-aeration created niches of facultative heterotrophs and anaerobic methanogens.